Blowfly Trypocalliphora braueri larvae infestation in Willow Warbler Phylloscopus trochilus nestlings on the Kola Peninsula, Russia - Matantseva, Maria; Simonov, Sergey; Eremeeva, Sofya (Ornis Svecica, 2025)
The blowfly Trypocalliphora braueri is a subcutaneous parasite infesting nestlings. We investigated the occurrence of blowfly larvae in Willow Warbler Phylloscopus trochilus nestlings on the Kola Peninsula, Russia, in 2023–2024. The infestation rate was 46.9% of nests and 37.9% of chicks. The highest infestation rates were observed during a season with a late beginning of bird breeding and an unusually warm summer. In the infested nests, 86.2% (28.6–100%) of nestlings contained 1–11 larvae. Chicks with many larvae or with vital organ damage died. Nestling survival in the infested nests decreased by 15.4% compared to that in uninfected nests, but these differences were not statistically significant. We also found no significant differences in infestation rates between areas with varying levels of anthropogenic pressure.